2021
DOI: 10.7759/cureus.13383
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Biomarkers for the Differential Diagnosis of Mild Acute Ischemic Stroke, Transient Ischemic Attack, and Stroke Mimic

Abstract: Introduction The differential diagnosis of transient ischemic attack (TIA) versus mild acute ischemic stroke (AIS) during the initial presentation to the emergency department is often difficult, as the diagnosis of both TIA and AIS relies on the presence of focal neurologic signs. As such, roughly 50% of patients with transient or mild neurologic deficits have an uncertain diagnosis prior to neuroimaging. Biomarkers, particularly leukocyte biomarkers, may be used by clinicians to diagnose mild AIS prior to neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous studies suggest that the AIS-associated inflammatory component is partly driven by the myeloid immune compartment, including microglia, peripheral monocytes, and macrophages ( 16 ). Numerous studies identified alterations in immune biomarkers in the cerebral spinal fluid (CSF) and blood that are associated with the severity and prognosis of AIS ( 17 ). However, few of these biomarkers are cell type-specific and thus provide limited information on cellular relevance in the pathogenesis of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that the AIS-associated inflammatory component is partly driven by the myeloid immune compartment, including microglia, peripheral monocytes, and macrophages ( 16 ). Numerous studies identified alterations in immune biomarkers in the cerebral spinal fluid (CSF) and blood that are associated with the severity and prognosis of AIS ( 17 ). However, few of these biomarkers are cell type-specific and thus provide limited information on cellular relevance in the pathogenesis of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this, people's interest in body fluid biomarkers for AIS mainly focused on diagnosis [ 9 , 10 ] and disease progression [ 11 , 12 ], but there was a lack of summary of prognostic-related body fluid biomarkers. It is worth noting that significant progress has been made in recent years in predicting neurological outcome, mortality, and post-stroke depression based on early body fluid biomarkers of AIS.…”
mentioning
confidence: 99%